2020
DOI: 10.1039/c9an01485c
|View full text |Cite
|
Sign up to set email alerts
|

Label-free detection of nosocomial bacteria using a nanophotonic interferometric biosensor

Abstract: Two methodologies using a BiMW biosensor have been developed for the fast, sensitive detection of P. aeruginosa and MRSA bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…For a proper oligonucleotide immobilization, the silicon nitride (Si 3 N 4 ) surface of the BiMW sensor was chemically modified with silane-PEG-COOH in order to generate a homogenous monolayer with anti-fouling properties and exposing reactive carboxyl groups [ 37 ]. For the activation of the silane-PEG-COOH monolayer, we employed the well-known EDC/NHS surface chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…For a proper oligonucleotide immobilization, the silicon nitride (Si 3 N 4 ) surface of the BiMW sensor was chemically modified with silane-PEG-COOH in order to generate a homogenous monolayer with anti-fouling properties and exposing reactive carboxyl groups [ 37 ]. For the activation of the silane-PEG-COOH monolayer, we employed the well-known EDC/NHS surface chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of sensitivity, we have also highlighted a number of techniques that successfully use interferometry to amplify the observation of bacterial presence. As is well known, phase-based measurements are among the most sensitive in photonics, so it is no surprise that this strategy is also successful in the detection and monitoring of a small number of bacteria, both for measuring low concentrations [68][69][70] and for assessing bacterial susceptibility to antibiotics [121].…”
Section: Discussionmentioning
confidence: 99%
“…Several improvements have since been made. For example, Maldonado et al [68,69] have demonstrated a bimodal waveguide for the detection of low concentrations of bacteria, that is, down to 40 CFU/mL. The device consists of an optical waveguide in Si 3 N 4 supporting two modes with different polarization, as schematically shown in Figure 2(a).…”
Section: Optical Waveguides and Interferometric Approachesmentioning
confidence: 99%
“…Very recent progress on BiMW biosensors reported identifying and quantifying nosocomial bacteria using specific receptors, which involves a silane‐PEG‐COOH coating as the bacteria‐repelling strategy to avoid extra blocking and reach fast (≈12 min) and accurate detection. [ 121 ]…”
Section: Silicon‐based Label‐free Optical Biosensorsmentioning
confidence: 99%